1987
DOI: 10.2337/diacare.10.5.567
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Metabolic Alterations by Insulin Supplements Administered Either Before or After 2-h Nocturnal Interruption of CSII

Abstract: To evaluate the efficacy of a bolus insulin injection to prevent the metabolic alterations induced by a 2-h nocturnal interruption of a continuous subcutaneous insulin infusion (CSII), nine type I (insulin-dependent) C-peptide-negative diabetic patients were studied from 2200 to 0800 h during two randomized tests. An insulin bolus (2.1 +/- 0.2 U) was administered via the pump either at 2300 h, just before CSII interruption, or at 0100 h, after reactivating the pump at its usual basal rate (1.05 +/- 0.11 U/h). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Finally, as expected, the duration of CSII interruption plays a crucial role. We demonstrated that 1-h pump arrest does not significantly alter the metabolic profile in well-controlled diabetic patients, while a 2-h period of CSII interruption is enough to induce a significant rise in plasma glucose and 3-OHB levels; in this condition, additional insulin boluses are required to prevent or correct the metabolic disorders [53].…”
Section: Interruption Of Csii With Regular Insulin: Comparison With Nmentioning
confidence: 86%
“…Finally, as expected, the duration of CSII interruption plays a crucial role. We demonstrated that 1-h pump arrest does not significantly alter the metabolic profile in well-controlled diabetic patients, while a 2-h period of CSII interruption is enough to induce a significant rise in plasma glucose and 3-OHB levels; in this condition, additional insulin boluses are required to prevent or correct the metabolic disorders [53].…”
Section: Interruption Of Csii With Regular Insulin: Comparison With Nmentioning
confidence: 86%